2000
DOI: 10.1046/j.1523-1739.2000.99383.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview, Critical Assessment, and Conservation Implications of Koala Distribution and Abundance

Abstract: Regional and national surveys provide a broadscale description of the koala's present distribution in Australia. A detailed understanding of its distribution is precluded, however, by past and continuing land clearing across large parts of the koala's range. Koala population density increased in some regions during the late 1800s and then declined dramatically in the early 1900s. The decline was associated with habitat loss, hunting, disease, fire, and drought. Declines are continuing in Queensland and New Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
164
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 20 publications
(29 reference statements)
1
164
0
1
Order By: Relevance
“…For example, the NGO Australian Koala Foundation estimates that the national population is 45000-80000 (25-50000 in Queensland and 10-15000 in both New South Wales and Victoria (Sharp 1995). This contrasts sharply with other estimates, for example 170000 in Queensland alone (G. Gordon, Queensland National Parks and Wildlife Service, personal communication), up to 10000 in New South Wales , and 75000-130000 for the Strathbogie Plateau in Victoria (Melzer et al 2000). The uncertainty of population estimates is further illustrated by Phillips (2000), who estimated koala abundance for the Strathbogie Ranges by modelling population growth from a known history of introductions and an expected rate of increase.…”
Section: States Of America and The Koala Is Now Listed As A Threatenementioning
confidence: 76%
See 2 more Smart Citations
“…For example, the NGO Australian Koala Foundation estimates that the national population is 45000-80000 (25-50000 in Queensland and 10-15000 in both New South Wales and Victoria (Sharp 1995). This contrasts sharply with other estimates, for example 170000 in Queensland alone (G. Gordon, Queensland National Parks and Wildlife Service, personal communication), up to 10000 in New South Wales , and 75000-130000 for the Strathbogie Plateau in Victoria (Melzer et al 2000). The uncertainty of population estimates is further illustrated by Phillips (2000), who estimated koala abundance for the Strathbogie Ranges by modelling population growth from a known history of introductions and an expected rate of increase.…”
Section: States Of America and The Koala Is Now Listed As A Threatenementioning
confidence: 76%
“…The most significant threat to the long-term conservation of koalas is habitat loss, although drought, wildfire, disease, predation and vehicle strikes are also serious threats (Melzer et al 2000). Despite these threats and the level of uncertainty regarding the abundance of koalas, it has been suggested that conservation intervention should be taken now, since there is clear evidence of decline in some populations while the existence of other robust populations offers the possibility of a variety of creative solutions (Sherwin et al 2000).…”
Section: States Of America and The Koala Is Now Listed As A Threatenementioning
confidence: 99%
See 1 more Smart Citation
“…The survival of the koala (Phascolarctos cinereus), an iconic Australian folivorous marsupial, is threatened by habitat loss, population fragmentation, motor-vehicle strike, predation by dogs and disease (Jackson et al, 1999;Melzer et al, 2000;McAlpine et al, 2006;Griffith et al, 2013). Koalas are currently distributed in the eastern states of Australia with additional isolated populations in South Australia (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Koala populations from Queensland and New South Wales (NSW) have also not experienced any systematic translocation and, relative to their southern counterparts, have high microsatellite diversity (Houlden et al, 1996). Although many northern populations are genetically distinct, as identified in south-east Queensland and north-east NSW (Lee et al, 2009(Lee et al, , 2012, this may be attributed to anthropogenic-related fragmentation and decline in many of these populations (Melzer et al, 2000;Gordon et al, 2006;Lunney et al, 2009). Northern populations were therefore listed as 'vulnerable' in early 2012 under the Australian federal Environment Protection and Biodiversity Conservation (EPBC) Act 1999.…”
Section: Introductionmentioning
confidence: 99%